Listening and question-asking behaviors in resident and nurse handoff conversations: a prospective observational study - Kannampallil, Thomas (JAMIA Open, 2020)
OBJECTIVE: To characterize interactivity during resident and nurse handoffs by investigating listening and question-asking behaviors during conversations. MATERIALS AND METHODS: Resident (n = 149) and nurse (n = 126) handoffs in an inpatient medicine unit were audio-recorded. Handoffs were coded based on listening behaviors (active and passive), question types (patient status, coordination of care, clinical reasoning, and framing and alignment), and question responses. Comparisons between residents and nurses for listening and question-asking behaviors were performed using the Wilcoxon rank-sum tests. A Poisson regression model was used to investigate differences in the question-asking behaviors between residents and nurses, and the association between listening and question-asking behaviors. RESULTS: There were no significant differences between residents and nurses in their active (18% resident vs 39% nurse handoffs) or passive (88% resident vs 81% nurse handoffs) listening behaviors. Question-asking was common in resident and nurse handoffs (87% vs 98%) and focused primarily on patient status, co-ordination, and framing and alignment. Nurses asked significantly more questions than residents (M(resident) = 2.06 and M(nurse) = 5.52) by a factor of 1.76 (P < 0.001). Unit increase in listening behaviors was associated with an increase in the number of questions during resident and nurse handoffs by 7% and 12%, respectively. DISCUSSION AND CONCLUSION: As suggested by the Joint Commission, question-asking behaviors were common across resident and nurse handoffs, playing a critical role in supporting resilience in communication and collaborative cross-checks during conversations. The role of listening in initiating question-asking behaviors is discussed.